The Effect of Human Resources Competence, Application of Local Government Accounting Systems, and Internal Control Systems on the Quality of Local Government Financial Reports - Ali Imransyah; M. Ardiansyah Syam; Syahril Djaddang (Budapest International Research and Critics University, 2022)
This research was conducted to determine the factors that effect the quality of local government financial reports. The factors were